2014
DOI: 10.12968/bjon.2014.23.17.942
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ experiences of the seasonal influenza vaccine in residential care

Abstract: The experience of nurses who work in the residential elderly care setting regarding the seasonal influenza vaccine is often overlooked, with a paucity of published qualitative studies. The aim of this study is to present an insight into the issues concerning nurses with regard to the seasonal influenza vaccine. The study purposively sampled registered nurses (n=11) working in a large long-term care facility for older people (n=142) in Ireland. Using a broad qualitative research approach, data were collected th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Many participants perceived themselves as at low risk of contracting influenza as they are healthy or ‘never get sick’ [ 12 25 ]. Some argued that they have a strong immune system due to working in healthcare and being exposed to infection [ 15 , 18 , 19 , 23 ]. Several studies reported a perception that high-risk populations comprise older people and people with chronic illnesses, not healthy working-age adults: [ 14 – 16 , 19 , 20 , 22 , 25 ] “what people get from the advertisements is you really only need it if you’re sick or in the nursing home or you have a lot of health issues” (participant [ 25 ]).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many participants perceived themselves as at low risk of contracting influenza as they are healthy or ‘never get sick’ [ 12 25 ]. Some argued that they have a strong immune system due to working in healthcare and being exposed to infection [ 15 , 18 , 19 , 23 ]. Several studies reported a perception that high-risk populations comprise older people and people with chronic illnesses, not healthy working-age adults: [ 14 – 16 , 19 , 20 , 22 , 25 ] “what people get from the advertisements is you really only need it if you’re sick or in the nursing home or you have a lot of health issues” (participant [ 25 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Many participants believed the vaccine was effective, and cited as reasons to accept vaccination: protecting patients against infection, particularly vulnerable groups such as older or immuno-compromised patients; [ 12 , 14 , 16 – 20 , 22 – 24 , 26 29 ] protecting their own health [ 12 , 14 17 , 19 , 20 , 22 – 24 , 28 , 29 ] or that of their families; [ 12 17 , 22 , 23 , 28 ] and avoiding time off work [ 12 , 14 18 , 23 , 24 , 29 ]. Few participants mentioned herd immunity or population health [ 16 , 17 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations